Plastics technology handbook - Chanda, Manas, 1940- (CRC Press, 2007)
This handbook continues to provide up-to-date coverage on the properties, processing methods, and applications of polymers. While retaining the easy-to-follow structure of the previous editions, this fourth edition covers advances in polymer-based nanomedicines, drug delivery, oxo-biodegradable polymers, polymer synthesis and applications, and the use of polymers in the automotive and aerospace industries, agriculture, electronics and electrical technology, and biomedical applications. It also includes more information on plastic foams and industrial polymers, including the emerging field of n.
Keywords: Plastics.; elektronické knihy; electronic books